Heterogeneous links between urban form and mobility: A comparison of São Paulo, Istanbul and Mumbai - Kandt, Jens (Journal of Transport and Land Use, 2018)
This paper presents determinants of travel demand in three important cities in emerging economies: São Paulo, Istanbul and Mumbai. By comparison, similarities and differences of travel demand among the cities are identified and discussed with regard to their geographical, institutional and spatio-physical conditions. Special attention is paid to the hitherto understudied impact of the built environment on travel in emerging economy cities. Drawing on identical household surveys carried out in each city, the study reveals that gender, social status, car ownership and geographical location are consistently associated with mode choice. Yet, the relative importance of those characteristics differs in each city in line with their distinct socio-cultural realities. Trip duration appears to be more affected by built-environment characteristics, once mode choice is taken into account. But, again, potential influences of the built environment operate in different ways in São Paulo, Istanbul and Mumbai. In particular, there appears to be a closer relationship between transport and land-use in Mumbai. The variation-finding, comparative design reveals plural associations of life situation, the built environment and travel, and thus evinces specific interactions that require contextual policy attention to achieve sustainable and inclusive urban mobility.